A descriptive analysis of children's playground injuries in the United States 1990-4. Issue 2 (June 1997) - Mack, M. G.; Hudson, S.; Thompson, D.
Abstract : OBJECTIVES: To review playground injury statistics over a five year period in order to develop an awareness of how and where children in the United States are being injured. METHODS: All data are based on the United States Consumer Product Safety Commission's National Electronic Injury Surveillance System (NEISS) for playground related injuries during 1990-4. The surveillance data includes injuries recorded in more than 90 hospital emergency departments located throughout the United States. RESULTS: Each year there are roughly 211, 000 preschool or elementary school-children in the United States who receive emergency department care for injuries associated with playground equipment. On average, 17 of these cases result in death. 70% of all injuries occur on public playgrounds, with nearly one third classified as severe. Swings, climbers, and slides are the pieces of playground equipment associated with 88% of all NEISS reported injuries. Falls to the surface are responsible for 70%. CONCLUSIONS: NEISS playground injury statistics contribute to our understanding of playground injuries. By identifying where and how children are injured, suggestions can be made in an attempt to make playgrounds safer.